Choosing Optimal Antibiotics for the Treatment of Patients Infected With Enterobacteriaceae: A Network Meta-analysis and Cost-Effectiveness Analysis - Han, Ruiying; Teng, Mengmeng; Zhang, Ying; Zhang, Tao; Wang, Taotao; Chen, Jiaojiao; Li, Sihan; Yang, Bo; Shi, Yaling; Dong, Yalin; Wang, Yan (Frontiers in Pharmacology, 2021)
Overuse of carbapenems has led to the increasing carbapenem-resistant Enterobacteriaceae. It is still unknown whether other antibiotics (especially novel β-lactam/β-lactamase inhibitor combinations [BL/BLIs]) are better than carbapenems in the treatment of Enterobacteriaceae. A systematic literature search was performed to identify randomized controlled trials (RCTs) assessing the efficacy and safety of any antibiotics on Enterobacteriaceae infections. We carried out a traditional paired meta-analysis to compare ceftazidime/avibactam to comparators. Network meta-analysis (NMA) was conducted to integrate direct and indirect evidence of all interventions. Moreover, cost-effectiveness analysis of antibiotics using a combined decision analytical Markov model was completed for the treatment of patients with complex urinary tract infection (cUTI). A total of 25 relevant RCTs were identified, comprising 15 different interventions. Ceftazidime/avibactam exhibited comparable efficacy and safety with comparators (carbapenems) in the paired meta-analysis. In the NMA, the surface under the cumulative ranking curve probabilities showed that in terms of efficacy, the interventions with the highest-ranking were meropenem/vaborbactam, meropenem, imipenem/cilastatin, ceftriaxone, ceftazidime/avibactam, and ceftolozane/tazobactam (but no significant difference between any two antibiotics [P>0.05]). Regarding safety, ceftazidime/avibactam had a higher incidence of adverse events than that of piperacillin/tazobactam (relative risk=0.74, 95% confidence interval=0.59 to 0.94). Based on drug and hospitalization costs in China, the incremental cost-effectiveness ratio per quality-adjusted life-year gained in the patients with cUTI for meropenem, ceftazidime/avibactam, and ceftolozane/tazobactam compared to imipenem/cilastatin were US579, US24569, and US29040, respectively. The ability of these BL/BLIs to serve as alternatives to carbapenems requires large-scale and high-quality studies to validate.